2019
DOI: 10.1016/j.fuel.2018.07.093
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feedstock origin and temperature on the structure and reactivity of char from pyrolysis at 1300–2800 °C

Abstract: This study reports the effect of feedstock origin, residence time and heat treatment temperature on CO 2 and O 2 reactivities, nanostructure and carbon chemistry of chars prepared at 1300, 1600, 2400 and 2800 • C in a slow pyrolysis reactor. The structure of char was characterized by transmission electron microscopy and Raman spectroscopy. The CO 2 and O 2 reactivity of char was investigated by thermogravimetric analysis. Results showed that the ash composition and residence time influence the char reactivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 46 publications
3
26
0
Order By: Relevance
“…The current investigation showed that decreasing electrical resistivity was primarily correlated to heat treatment temperature, bulk density, and temperature profile inside the bulk, whereas prolonging the residence time did not affect electrical resistivity. At 1600 • C, the charcoal structure comprises amorphous and nanocrystalline graphite, in which prolonging residence time to 12 h led to the formation of ring graphitic structures [21]. However, the increase in crystallite growth is compensated by a decrease in excess electrons [1], which resulted in a quasi-constant electrical resistivity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current investigation showed that decreasing electrical resistivity was primarily correlated to heat treatment temperature, bulk density, and temperature profile inside the bulk, whereas prolonging the residence time did not affect electrical resistivity. At 1600 • C, the charcoal structure comprises amorphous and nanocrystalline graphite, in which prolonging residence time to 12 h led to the formation of ring graphitic structures [21]. However, the increase in crystallite growth is compensated by a decrease in excess electrons [1], which resulted in a quasi-constant electrical resistivity.…”
Section: Discussionmentioning
confidence: 99%
“…The molar H/C and O/C ratios decreased by the thermal decomposition and release of volatile oxygenates, such as organic acids, alcohols, and phenols as well as hydrogen, methane, carbon monoxide, and carbon dioxide [39,40]. Dehydrogenation reaction at high temperature can form small aromatic cluster in the carbon matrix [20,21], in which the increased number of clusters result in an enhanced aromaticity of the solid residue. Ultimate analysis verified results from proximate analysis that solid residue is composed of carbon and inorganic matter.…”
Section: Product Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that co-pyrolysis and distillation of charcoal with tar significantly increase the solid char yield in the entire process and thus, emphasize the potential use of biocarbon-based reductants in ferroalloy industries. It was found that the maximum reaction rate of charcoal from additional pyrolysis at 1300 and 1600 • C was shifted to temperatures about 40 • C lower than for charcoals from primary pyrolysis at 1300 • C. The TEM analysis showed that the mean separation distance of oak char graphene layers was similar to graphite, whereas spruce char contained different types of amorphous carbon structures [31]. However, in the present study the CO 2 reactivity of spruce and oak charcoal samples was similar after the additional heat treatment.…”
Section: Product Yieldsmentioning
confidence: 97%
“…The main difference in O 2 and CO 2 reactivity of lignin samples was observed in the higher maximum temperature of PL compared to other lignin samples due to the shift of the DTG peak to the higher temperatures. The DTG curves show a double broad peak that indicates a heterogeneous lignocellulosic mixture with respect to O 2 and CO 2 reactivity [50,51].…”
Section: Thermogravimetric Analysismentioning
confidence: 99%